Verslag van the first international lesbian/gay health conference "toward diversity" including : the third aids forum June 16-19, 1984 - Brühl, Karel (Amsterdam : Stichting Aanvullende Dienstverlening Homogroep Gezondheidszorg Amsterdam European Gay Health Care, 1984)
Fonds Suzan Daniel (FSD)
Nederlands
Artikel